MANAJEMEN STRATEGI DALAM INOVASI PEMBELAJARAN BERBASIS KEWIRAUSAHAAN UNTUK MENINGKATKAN KOMPETENSI EKONOMI SANTRI DI ERA 4.0 - Shalahuddin, M.; Nurobiyanto; Miqdad Arromy, Muhammad; Hidayat, Ara (Sindoro: Cendikia Pendidikan, 2024)
This study aims to analyze the strategic management of entrepreneurship-based learning innovation at SMA IT Nurul Fajri, Cikarang Barat, Bekasi, to improve students' economic competencies in the era of the Fourth Industrial Revolution. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, direct observations, and document studies. The findings reveal that strategic management is carried out in three main stages: planning, implementation, and evaluation. In the planning stage, the school designs an entrepreneurship program integrating Project-Based Learning (PjBL) and digital technology, such as marketplace platforms (Shopee, Tokopedia) and social media (Instagram, Facebook). The implementation stage involves hands-on practice and real-world projects that develop students' entrepreneurial skills, including the use of digital technology for marketing and transactions. Evaluation is conducted through process and outcome assessments, focusing on the success of entrepreneurial projects and the reinforcement of Islamic economic values. This study concludes that entrepreneurship-based learning innovation strategies are effective in enhancing students' economic competencies, particularly in practical skills, digital technology proficiency, and strengthening ethical Islamic business principles. Keywords: Strategic Management, Learning Innovation, Entrepreneurship, Economic Competence, Fourth Industrial Revolution.